2018
DOI: 10.3389/fpsyg.2018.02357
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Affective Correlates of Chinese Children’s Mathematical Word Problem Solving

Abstract: Mathematical word problem solving (MWPS) involves multiple steps, including comprehending the problem statements, determining the arithmetic operations that have to be performed, and finding the answers. This study investigated the relative contributions of different cognitive and affective variables to children’s MWPS. To achieve this goal, 116 third-grade Chinese children were tested. Results showed that after controlling for age and non-verbal intelligence, the abilities to solve direct and indirect mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Moreover, cognitive flexibility has a non‐significant correlation with closed problem solving, consistent with some previous findings (e.g., Coulanges et al, 2021; Zhang et al, 2018). For closed problems with fixed solving routines that can be recalled directly, there may be an inhibitory effect of cognitive flexibility on switching procedures or strategies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, cognitive flexibility has a non‐significant correlation with closed problem solving, consistent with some previous findings (e.g., Coulanges et al, 2021; Zhang et al, 2018). For closed problems with fixed solving routines that can be recalled directly, there may be an inhibitory effect of cognitive flexibility on switching procedures or strategies.…”
Section: Discussionsupporting
confidence: 91%
“…Intelligence is an important factor for solving mathematical closed problems (Bahar & Maker, 2015; Lechner et al, 2019; Zhang et al, 2018). For example, many cross‐sectional research found that worldwide, from children to adults, a person's intelligence level has a stable correlation with their problem‐solving ability (e.g., Farrington‐Flint et al, 2007; Lechner et al, 2019).…”
Section: Cognitive Factors For Solving Closed Math Problemsmentioning
confidence: 99%
“…Not only on mathematics performance, but mathematics anxiety was also found with a negative effect on student mathematics-related cognitive skills (Wu et al, 2017;Maloney and Retanal, 2020), especially on problem-solving skills (Pajares and Kranzler, 1995;Pajares, 1996;Zhang et al, 2018;Ozcan and Gumus, 2019;Passolunghi et al, 2019;Zhou et al, 2020). The development of problem-solving skills is considered mainly related to the mathematics domain.…”
Section: Literature Review Mathematics Anxietymentioning
confidence: 99%
“…Compared to simple mathematics tasks, it is highly likely to observe mathematics anxiety when students were involved in complex tasks requiring problem-solving skills (Wu et al, 2012;Ching, 2017). Previous research found that high mathematics anxiety disrupted students' working memory resources and impeded their problem-solving performance (Beilock, 2008;Alamolhodaei, 2009;Buelow and Frakey, 2013;Ramirez et al, 2013Ramirez et al, , 2016Trezise and Reeve, 2014;Zhang et al, 2018;Liu et al, 2019).…”
Section: Literature Review Mathematics Anxietymentioning
confidence: 99%
See 1 more Smart Citation